2013
DOI: 10.2139/ssrn.2258392
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Distribution and Correlates of an Entrepreneurship-Prone Personality Profile in the United States, Germany, and the United Kingdom: A Socioecological Perspective

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 97 publications
5
85
1
5
Order By: Relevance
“…Empirical evidence shows that East Germans have a higher level of state-reliance when compared to West Germans (e.g., Alesina and Fuchs-Schuendeln, 2007), which feeds back into lower preferences for entrepreneurship among Easterners (Bauernschuster et al, 2012;Runst, 2013). Furthermore, Obschonka et al (2013) find that the Big Five personality characteristics differ between West and East Germans whereby the latter are less likely to have an entrepreneurial personality profile. These findings might be explained to a large degree by anti-capitalist indoctrination in socialism, leading to the formation of norms and values that are at odds with entrepreneurship (e.g., Earle and Sakova, 2000;Schwartz and Bardi, 1997;Smallbone and Welter, 2001).…”
Section: Settingmentioning
confidence: 85%
“…Empirical evidence shows that East Germans have a higher level of state-reliance when compared to West Germans (e.g., Alesina and Fuchs-Schuendeln, 2007), which feeds back into lower preferences for entrepreneurship among Easterners (Bauernschuster et al, 2012;Runst, 2013). Furthermore, Obschonka et al (2013) find that the Big Five personality characteristics differ between West and East Germans whereby the latter are less likely to have an entrepreneurial personality profile. These findings might be explained to a large degree by anti-capitalist indoctrination in socialism, leading to the formation of norms and values that are at odds with entrepreneurship (e.g., Earle and Sakova, 2000;Schwartz and Bardi, 1997;Smallbone and Welter, 2001).…”
Section: Settingmentioning
confidence: 85%
“…Specifically, using the state-level personality scores published by Rentfrow and colleagues (2008), studies have shown that state-level personality scores are related to health and morbidity (McCann, 2010a(McCann, , 2010b(McCann, , 2011bPesta, Bertsch, McDaniel, Mahoney, & Poznanski, 2012;Voracek, 2009), psychological well-being (McCann, 2011aPesta, McDaniel, & Bertsch, 2010;Rentfrow, Mellander, & Florida, 2009), social capital (Rentfrow, 2010, creative capital (Florida, 2008), income inequality (de Vries, Gosling, & Potter, 2011), entrepreneurship rates (Obschonka, Schmitt-Rodermund, Silbereisen, Gosling, & Potter, 2013), political values (Rentfrow, Jost, Gosling, & Potter, 2009), and regional stereotypes (Rogers & Wood, 2010). These findings suggest that the personality traits that are common in a state are linked to an assortment of important indicators that delineate different regions of the United States.…”
Section: Regional Variation In Personalitymentioning
confidence: 99%
“…This paper places emphasis on one particular element: the size of businesses already in the region where the entrepreneur resides. However, other elements, such as financial capital and the market structure (Colombo and Grilli 2005;Mata 1996), the presence of role models (Bosma et al 2012), the economic context, and an entrepreneurial culture (Stuetzer et al 2014), or even the distribution of personality traits (Obschonka et al 2013) also matter. Lack of consideration of these regional-level idiosyncrasies may lead to inefficient or erroneous policies (McCann and OrtegaArgilés 2016).…”
Section: Discussionmentioning
confidence: 99%